Numerical Investigation on Auxiliary Heat Sources for Horizontal Ground Heat Exchangers - Alexandru-Mihai BULMEZ; Vasile CIOFOAIA; Gabriel NĂSTASE; George DRAGOMIR; Alin-Ionuț BREZEANU; Nicolae-Fani IORDAN; Sorin-Ionuț BOLOCAN; Mariana FRATU; Costel PLEȘCAN; Christiana Emilia CAZACU; Ovidiu DEACONU (MDPI; Buildings, 2022)
Human interference with the Earth’s climate cannot be ignored any longer. Renewable energy sources need utmost attention in all energy sectors. For buildings, geothermal energy for heating, cooling, and domestic hot water is a sustainable solution. Horizontal ground heat exchangers (HGHE) demonstrate promising results with low installation costs. Research is focused on increasing their thermal performances by structural improvements and ground thermal proprieties improvements, with little research on using auxiliary heat to increase their performances. A numerical model for an HGHE was established to investigate the effects of auxiliary heat sources on the performances of the HGHE. The results demonstrate that heat transfer into the HGHE increases the overall ground temperature at the end of the heating season by 138.50% compared with no heat transfer from auxiliary heat sources. The ground freezing period decreased by approximately 24.74% by having a heated basement, approximately 40.20% by transferring heat with solar thermal panels, and approximately 62.88% by using both auxiliary heat sources. The difference between the undisturbed ground temperature and the ground temperature with no auxiliary heat sources at the end of the season was 3.45 C. The difference between the undisturbed ground temperature and the ground temperature with all auxiliary heat sources resulted in 0.92 °C.